PERANCANG PROGRAM KAMPANYE “BERSINAR” POLDA JATIM DENGAN TEKNIK SERIES CAMPAIGNDALAM UPAYA MEMBERANTAS NARKOBA - Apriannoor, Ilham; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
Now the government is intensively combating drugs , the government gave orders to every ministry / agency fight against drugs . Given the order , the police area of East Java ( East Java Police ) also participate in helping to combat drugs in the program " Shine ( Clean Brush Drugs) " , but if only the police alone is not the role of the community to help inform the drug eradication will be very long in eradicating . The purpose of this thesis to design a campaign program "shine" East Java Police with engineering series campaign in an effort to combat drugs..Keywords: Bersinar campaign, Media Promotion, information, combat drugs.